Gender, Land and Food Access in Ghana’s Suburban Cities: A Case of the Adenta Municipality - Kwaku Owusu Twum; Kwabena Asiama; John Ayer; Cosmas Yaw Asante (Land, 2020)
The disparity in land and food access in Ghana often overlooks the possibility of an underlying gender disparity. This paper explores and interrogates the disparity between land and food access with respect to gender and the evolution of this relationship over the years as a result of the settlement expansion and urban growth within the Adenta Municipality in Ghana. Adopting a mixed pairwise approach of combining spatial analytical tools, vulnerability indexing and resilient indicators, the paper examines the levels and rates of land accessibilities within the stream of modern cities. It assesses the land market system complexities within developing economies and attempts to address the potential threats of gender-land access gaps. The paper finally assigns weights of ranks to model the phenomenon and recommends trends that can facilitate predictions and early cautionary systems for effective urban land governance in Ghana. The paper concludes that though it is noticed that women engage in power structures on a daily basis, this both benefits and burdens them, depending on their socio-cultural status and other factors in terms of access to land and food.